Pengaruh Promosi dan Harga terhadap Minat Beli Ulang Konsumen pada Aplikasi Gofood (Studi Kasus pada Mahasiswa PIPS FKIP Universitas Riau) - Gultom, Astrid Eleora; Indrawati, Henny; Mujiono, Mujiono (Universitas Mataram, 2025)
This study aims to analyze the influence of promotions and prices on repeat purchase intention of consumers on the Gofood application. The study population consists of active undergraduate students from the 2021-2023 cohort of the Social Studies Education Department at the Faculty of Teacher Training and Education, University of Riau, who have made at least three purchases on the Gofood application, with a sample of 59 students. The sample was selected using proportional random sampling and the Slovin formula. Data were collected through questionnaires and analyzed using descriptive analysis and multiple linear regression. The results show that promotions on the Gofood application are categorized as excellent, prices are affordable, and the repeat purchase intention of consumers is high. Both promotion and price have a simultaneous effect on repeat purchase intention. Individually, promotion has a positive and significant effect, as does price. The contribution of promotion and price to repeat purchase intention is 40.5%, while the remaining 59.5% is influenced by other variables not included in the regression, such as product ratings, app usability, service quality, website quality, brand image, and product quality.